2021
DOI: 10.1002/etc.5007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to Environmental DDT/DDE in 2 Species of Small Rodents: Measures of Contaminant Load, Immune Dysfunction, and Oxidative Stress

Abstract: Persistent contaminants are ubiquitous in our water and soil, and thus chronic exposure to environmentally relevant levels of these contaminants may pose a risk to humans and wildlife. Two species of small mammals (deer mouse, Peromyscus maniculatus and cotton rat, Sigmodon hispidus) were collected from historically dichlorodiphenyltrichloroethane (DDT)-contaminated and reference areas at the Redstone Arsenal (Huntsville, AL, USA), a US Environmental Protection Agency (USEPA)-designated Superfund site. Soil sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
1
3
0
1
Order By: Relevance
“…One exception was the congener PCB‐156, which suggests there may be a local, legacy source of PCBs to the environment in Victoria, which requires further investigation. Generally, OCPs had a low detection rate, but DDE exposure was still relatively high and consistent with worldwide literature, indicating that DDT breakdown products are still a global issue (Molina et al, 2021). In addition, there has been recent discussion of the dangerous nature of ongoing poorly related use of pesticides in Australia (Schneider, 2021).…”
Section: Discussionsupporting
confidence: 81%
“…One exception was the congener PCB‐156, which suggests there may be a local, legacy source of PCBs to the environment in Victoria, which requires further investigation. Generally, OCPs had a low detection rate, but DDE exposure was still relatively high and consistent with worldwide literature, indicating that DDT breakdown products are still a global issue (Molina et al, 2021). In addition, there has been recent discussion of the dangerous nature of ongoing poorly related use of pesticides in Australia (Schneider, 2021).…”
Section: Discussionsupporting
confidence: 81%
“…Es importante resaltar que la exposición prolongada a insecticidas puede ser perjudicial para la salud, teniendo en cuenta que dentro de la población del estudio la mayoría tenias más de 10 años de ambigüedad. Estudios recientes indicaron que la exposición crónica a niveles ambientales relevantes puede representar un riesgo para los humanos y la vida silvestre, provocando disfunción inmunitaria y estrés oxidativo (Molina et al, 2021). Así mismo, Moura et al, (2020) en una investigación de revisión bibliográfica encontraron tres casos de neoplasias hematológicas asociadas a la exposición por malatión, en discrepancia con Hu et al, (2017) quienes no encontraron relación estadísticamente significativa en asociación con linfoma no Hodgkin.…”
Section: Discussionunclassified
“…In addition, Blanco-Munoz et al [7] documented effects of chronic DDT exposure in humans at the gonadal, pituitary, and hypothalamic levels, indicating that the mechanisms by which DDT causes its effects are still unclear and require further study. To explore the potential mechanisms of action seen in our previous field and lab studies [8], we exposed male rats to environmentally relevant DDE doses extrapolated from our field study [9]. We found that DDE exposure of prepubertal (21–35 days of age) and pubertal rats (35–49 days of age) caused animals at both age groups to exhibit decreased serum T and testicular T production in a nonmonotonic dose–response that has been reported for many endocrine disruptors [9, 10].…”
Section: Introductionmentioning
confidence: 99%